Monitoring antibiotic residues in honey - Monica Cristina Cara; Gheorghita Simion; Panfiloiu Mirabela; Harieta Pirlea (Medicamentul Veterinar, 2011)
Next to the beta-lactam antibiotics in veterinary medicine, streptomycin is one of the mostly used antibiotics. High concentration of streptomycin could lead to ototoxic and nephrotoxic effects. Low concentration – as found in food – may cause allergies, destroy the intestinal flora and favor immunity to some pathogenic microorganisms. In 1948 chlortetracycline was isolated by Duggan as a metabolite and this was the first antibiotic substance of the group of tetracyclines. In the present paper there are presented the monitoring of the antibiotic residues in honey from Timis County. The residues of tetracycline and streptomycin in honey were determined by the method ELISA – a quantitative method of detection. The microtitre wells are coated with tetracycline and anti-streptomycin antibodies. Free antibiotic and immobilized antibiotic compete with the added antibiotic antibody (competitive immunoassay reaction). Any unbound antibody is then removed in a washing step. Bound conjugate enzymes convert the colorless chromogen into a blue product. The addition ofthe stop reagent leads to a color change from blue to yellow. The measurement is made photometrically at 450 nm. The absorption is inversely proportional to the antibiotic concentration in the sample.